EDUKASI KESEHATAN REPRODUKSI REMAJA PADA SISWA KELAS XII SMP NEGERI 2 GLENMORE: Pendekatan Edutainment untuk Meningkatkan Pengetahuan Pubertas dan Personal Hygiene - Ineke Permatasari; Tria Eni Rafika Devi; Regina Ayu Fristiyanti; Suci Fitriana Pramudya Wardani (PPPM Stikes Banyuwangi, 2026)
Early adolescence represents a critical developmental stage characterized by rapid physical, hormonal, and psychological changes. These transitions often trigger anxiety, confusion, and misconceptions among students, particularly when accurate and age-appropriate reproductive health information is limited. At SMP Negeri 2 Glenmore, preliminary observations revealed that many ninth-grade students lacked basic knowledge about puberty, such as nocturnal emissions among boys or the normal menstrual cycle among girls. This community service program aimed to evaluate the effectiveness of the edutainment approach in improving adolescents’ reproductive health knowledge. The intervention combined short lectures delivered in everyday language, small group discussions, interactive quizzes, and an anonymous question box to create a safe and engaging learning environment. A total of 42 students participated, and their knowledge was assessed using a 20-item questionnaire with established validity (0.71–0.89) and reliability (Cronbach’s alpha = 0.85). Results demonstrated a substantial improvement: the proportion of students with good knowledge increased from 14.3% to 88.1%, with mean scores rising from 10.1 to 16.7. The highest gain was observed in the personal hygiene domain (+75%), followed by psychological aspects and risk-prevention behaviors. Anonymous questions revealed students’ genuine concerns, ranging from physiological changes to moral perceptions, underscoring the importance of open and non-judgmental communication. The findings suggest that edutainment is not only effective but also practical, low-cost, and replicable as a routine program within school counseling and health units. In conclusion, reproductive health education delivered through edutainment fosters knowledge, confidence, and healthy attitudes among adolescents, making it a valuable strategy for sustainable school-based health promotion